OS PARQUES EMPRESARIAIS NO CONTEXTO DO DESENVOLVIMENTO REGIONAL DO MARANHÃO: Uma análise sobre o Parque Empresarial de Timon - SOARES, Reginaldo Muniz (2023)
This master's dissertation aims to analyze the effects of the Parque Empresarial de Timon on the regional development of Maranhão, based on the productive specialization of the subclasses of companies located in the Parque Empresarial de Timon. The spatial scope of the study is the Parque Empresarial de Timon, and the temporal scope is the period from 2010 to 2020. The research conducted is characterized as a descriptive study with both qualitative and quantitative aspects, utilizing data collected through bibliographic and documentary research. The theoretical framework supporting the analysis draws upon regional development theories (Perroux, 1955; Myrdal, 1957; Hirschman, 1958) and business clusters theories (Marshall, 1890; Becattini, 1990). The Quociente Locational (QL) methodology was employed, using the Immediate Geographic Region (RGI) of Timon as the basis, derived from the RAIS (2020) data. Regarding productive specialization, the analysis indicated that 80% of the companies established in the Parque Empresarial de Timon belong to subclasses in which the RGI of Timon demonstrates expertise. It was observed that the limited presence of companies in the Parque Empresarial de Timon (4%) restricts the park's impact on regional development, particularly concerning job creation and income generation.